MENINGKATKAN PERAN PEMANGKU KEPENTINGAN DALAM PENGELOLAAN WILAYAH HULU DAERAH ALIRAN SUNGAI CILIWUNG - Iis Alviya; Elvida Yosefi Suryandari; Retno Maryani; Zahhrul Muttaqin (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2016)
Stakeholders have a ver y important role interm of the management of upstream watershed. Thus, the common understanding on the existence and role of stakeholders is an important factor in order to achieve good governance of watershed management, leading to the attainment of environmental, social and economic benefits. This paper aims to analyse the role, interests, and cooperation among stakeholders and its relationship with the condition of upper Ciliwung watershed. Stakeholder analysis was used in this study to identify stakeholders, to categorize them, and to investigate the relationship between stakeholders. The analysis showed the lack of cooperation among stakeholders both between key stakeholders with primar y stakeholders. This resulted in lack of communities' understanding on the benefits and the importance of conservation activities in the upstream Ciliwung watershed. Meanwhile, the cooperation between key stakeholders and supporting stakeholders, especially the providers of funds, was relatively better/stronger. This can be seen from a better management of inter-agency cooperation in the upstream Ciliwung watershed, although the effort was tend to be project-oriented. Therefore, communication forum need to be established, to taking role for synchronizing , collaborating and coordinating stakeholders' efforts, so that the management programs of upstream Ciliwung watershed can be integrated.